Superfamily II helicases: the potential therapeutic target for cardiovascular diseases - Fang, Tianxiang; Wang, Xizhi; Huangfu, Ning (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVDs) still maintain high morbidity and mortality globally. Helicases, a unique class of enzymes, are extensively implicated in the processes of nucleic acid (NA) metabolism across various organisms. They play a pivotal role in gene expression, inflammatory response, lipid metabolism, and so forth. However, abnormal helicase expression has been associated with immune response, cancer, and intellectual disability in humans. Superfamily Ⅱ (SFⅡ) is one of the largest and most diverse of the helicase superfamilies. Increasing evidence has implicated SFⅡ helicases in the pathogenesis of multiple CVDs. In this review, we comprehensively review the regulation mechanism of SFⅡ helicases in CVDs including atherosclerosis, myocardial infarction, cardiomyopathies, and heart failure, which will contribute to the investigation of ideal therapeutic targets for CVDs.